A simplicidade como critério de hipóteses científicas: a abordagem naturalista de W. V. O. Quine - Acrissio Luiz Goncalves (2016)
My aim in this dissertation is to discuss Quines understanding of the problem of simplicity of scientific hypotheses, i.e., the problem of justifying the choice of a hypothesis or scientific theory based on the (comparative) determination of simplicity of his postulates/statements. I argue that simplicity is justified simply because it is strongly rooted in scientific practice. In the first chapter, I present the general aspects of Quines philosophical thought, highlighting positions which constitute the core of his philosophical system and that serve as a basis to the treatment of the issue of simplicity, i.e., naturalism and holism. In the second chapter, I present a partial answer to the question regarding how we evaluate a given hypothesis or scientific theory, approaching the criteria from which we made use for such an evaluation, viz.: precision, conservatism, modesty, generality, refutability and simplicity. In the third chapter, I evaluate Quines naturalistic defense of simplicity grounded in several neurobiological explanations for our propensity to simplicity. I maintain that the pragmatic posture Quine adopts dissolves the border between epistemic and pragmatic explanations for the adoption of simplicity in the scientific praxis.